2021
DOI: 10.1017/s0954579421000882
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional profiles of autism spectrum disorders, attention deficit hyperactivity disorder, and disinhibited and reactive attachment disorders: a symptom comparison and network approach

Abstract: Children with autism spectrum disorders (ASDs), attention deficit hyperactivity disorder (ADHD) and disinhibited and reactive attachment disorders (RAD/DAD) often experience socioemotional problems. Elucidating a clear picture of these profiles is essential. Strengths and Difficulties Questionnaires (SDQs) were analysed from cohort of children with ASD (n = 1430), ADHD (n = 1193), and RAD/DAD (n = 39). Kruskal–Wallis Tests and network analytic techniques were used to investigate symptom profiles. Children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In the case of children with special educational needs, it is possible that the lack of significant differences is due to the small number of children in our sample. It could also be because the strategies used are generic and some of these children need a specific therapeutic intervention for the recognition of emotions, social cognition, and putting oneself in another’s place, etc., due to deficiencies in these surroundings, as occurs in children on the ASD [ 31 , 32 , 33 ]. Likewise, in children with ADHD, difficulties in self-regulation and high emotional reactivity have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of children with special educational needs, it is possible that the lack of significant differences is due to the small number of children in our sample. It could also be because the strategies used are generic and some of these children need a specific therapeutic intervention for the recognition of emotions, social cognition, and putting oneself in another’s place, etc., due to deficiencies in these surroundings, as occurs in children on the ASD [ 31 , 32 , 33 ]. Likewise, in children with ADHD, difficulties in self-regulation and high emotional reactivity have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…The insights of clinicians will be essential to the meaningful interpretation of such clusters of symptoms, and advancement from the identification to the design of interventions. Recently we have used the network approach to explore socioemotional profiles in children and young with autism and ADHD (Coughlan et al, 2021). However, due to the sample size we were unable to compare networks for children with attachment disorders.…”
Section: Discussionmentioning
confidence: 99%
“… Skellern et al, 2005 ) who have suggested that structuring services to meet individual needs, rather than specific diagnoses, is a laudable goal. Using symptom mapping approaches ( Borsboom & Cramer, 2013 ; Coughlan et al, 2021 ) and applying these to service configuration might be a fruitful approach. However, there is enthusiasm for more dimensional approaches to neurodevelopment with programmes such as Research Domain Criteria looking promising ( Clark et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%